2009
DOI: 10.1590/s1516-05722009000200008
|View full text |Cite
|
Sign up to set email alerts
|

Xanthium strumarium L. antimicrobial activity and carboxyatractyloside analysis through electrospray ionization mass spectrometry

Abstract: ABSTRACT:The aim of this work was to evaluate the antimicrobial activity of Xanthium strumarium L. leaf extracts against Staphylococcus aureus, Escherichia coli, Salmonella typhimurium, Pseudomonas aeruginosa and Clostridium perfringens, as well as to investigate the presence of the toxic compound carboxyatractyloside in different plant parts. S. aureus and C. perfringens were more sensitive to non-polar than to polar fractions, and there was no difference between extracts for the remaining bacteria. All extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Carboxyatractyloside causes hypoglycemia in animals that consume it probably because it causes uncoupling of oxidative phosphorylation. 28,29 In our study, we postulate that carboxyatractyloside and Xanthatin substances caused the insecticidal effect although the effective substance of extracts has been not determined. The extract of A. wilhelmsii (C) had the highest acaricidal and insecticidal effect on T. urticae, L. decemlineata.…”
Section: Discussionmentioning
confidence: 80%
“…Carboxyatractyloside causes hypoglycemia in animals that consume it probably because it causes uncoupling of oxidative phosphorylation. 28,29 In our study, we postulate that carboxyatractyloside and Xanthatin substances caused the insecticidal effect although the effective substance of extracts has been not determined. The extract of A. wilhelmsii (C) had the highest acaricidal and insecticidal effect on T. urticae, L. decemlineata.…”
Section: Discussionmentioning
confidence: 80%
“…Similar to our findings, a potential against Gram-negative bacteria was also observed by Ghahari et al in fruit essential oil of the species X. strumarium L. [ 25 ]. Scherer et al reported no differences between antimicrobial potential against S. aureus , E. coli , and P. aeruginosa strands for hydroalcoholic SE leaf extracts of X. strumarium L.; however, the extracts exhibited strong overall antimicrobial activity [ 26 ]. Similar activity against S. aureus was reported by Ingawale et al for methanolic X. strumarium L. fruit extracts [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CATR may be undetectable in fully grown leaves and mature spiny involucres (burs without true dry fruits), but achenes, which are very often mistakenly referred to as seeds, enclosing a single kernel and cotyledonary-stage leaves are the source of this toxin in X. strumarium (Scherer et al. 2009 ). A complicating finding of an earlier X. strumarium analysis was the presence of CATR in integral burs at a significantly higher concentration, i.e., 4.57 mg/g, than that detected in very young seedlings at the two leaf-like phase, i.e., 1.2 mg/g (Cole et al.…”
Section: Toxicity Of Atractyloside- and Carboxyatractyloside-containi...mentioning
confidence: 99%